Intersected functional zone of transcriptional regulators patterns stemness within stem cell niche of root apical meristem. Issue 7 (2nd March 2020) - Xu, Meizhi; Gu, Xu; Liang, Nengsong; Bian, Xinxin; Wang, Hong; Qin, Yaxin; Pi, Limin; Wu, Shuang
Abstract: Root stem cell niche (SCN) consists of a quiescent center (QC) and surrounding stem cells. Disrupted symplastic communication leads to loss of stemness in the whole SCN. Several SCN regulators were reported to move between cells for SCN maintenance. However, single mutant of these regulators is insufficient to abolish QC stemness despite the high differentiation rate in surrounding stem cells. To dissect the mechanism behind such distinct stemness in SCN, we combined the mis‐expression strategy with pWOX5:icals3m system in which QC is symplastically isolated. We found the starch accumulation in QC could be synergistically repressed by WUSCHEL‐RELATED HOMEOBOX 5 (WOX5), SHORT‐ROOT (SHR), SCARCROW (SCR), and PLETHORA (PLT). Like PLTs, other core regulators also exhibited dimorphic functions by inhibiting differentiation at a higher dose while promoting cell division at a low protein level. Being located in the center of the intersected expression zones, QC cells receive the highest level of core regulators, forming the most robust stemness within SCN. WUSCHEL‐RELATED HOMEOBOX 5 was sufficient to activate PLT1/2 expression, contributing to the QC‐enriched PLTs. Our results provide experimental evidence supporting the long‐standing hypothesis that the combination of spatial expression, synergistic function and dosage effect of core regulators result in spatially distinct stemness in SCN. Abstract : This study provides a putative mechanism behind spatially distinct stemness within root stem cell niche. Quiescent Cell (QC) differentiation could be synergistically repressed by a set of transcription factors, resulting in the highest stemness. WOX5 activates PLTs, contributing to their QC?enrichment. These regulators exhibited dimorphic functions in a dose‐dependent manner.